The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/ie050356p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of THF on Equilibrium Pressure and Dissociation Enthalpy of CO2 Hydrates Applied to Secondary Refrigeration

Abstract: The present work investigates the formation conditions and the latent heat of dissociation of hydrates formed from tetrahydrofuran (THF)-CO 2 -water mixtures. The conditions investigated are 3.8-15 wt % for THF concentration and 0.2-3.5 MPa for the CO 2 partial pressure range, conditions that are adapted to the use of the corresponding hydrate slurries as secondary refrigerants. Both differential thermal analysis (DTA) and differential scanning calorimetry (DSC) methods were used for the experimental determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(161 citation statements)
references
References 17 publications
8
149
1
3
Order By: Relevance
“…However, only a few publications provide detailed phase equilibrium data for the ternary system of water, THF and CO 2 , especially at low temperatures and THF concentrations of approximately 17.4 mass percent (5 mole percent) in the aqueous phase (Delahaye et al, 2006;Sabil et al, 2010;Seo et al, 2008). Such data can provide information on the true ability of THF promoted sII hydrates to incorporate sufficient amounts of CO 2 in order to establish a feasible capture process operating at temperatures close to the freezing point of water.…”
Section: Tetrahydrofuran -A Hydrophilic Hydrate Promotermentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few publications provide detailed phase equilibrium data for the ternary system of water, THF and CO 2 , especially at low temperatures and THF concentrations of approximately 17.4 mass percent (5 mole percent) in the aqueous phase (Delahaye et al, 2006;Sabil et al, 2010;Seo et al, 2008). Such data can provide information on the true ability of THF promoted sII hydrates to incorporate sufficient amounts of CO 2 in order to establish a feasible capture process operating at temperatures close to the freezing point of water.…”
Section: Tetrahydrofuran -A Hydrophilic Hydrate Promotermentioning
confidence: 99%
“…Hence it is of interest to investigate how binary hydrate systems of THF and CO 2 behave in the low temperature region, not only with respect to the inclusion of CO 2 in the solid phase but also with respect to the pressure requirements needed to form mixed hydrates at these conditions. Delahaye et al (2006) measured hydrate dissociation P-T conditions as well as heats of dissociation for the ternary system of water, THF and CO 2 . In addition, the T-x diagram for the binary sub-system of water and THF was experimentally determined at atmospheric pressure for reference and for modeling purposes.…”
Section: Tetrahydrofuran -A Hydrophilic Hydrate Promotermentioning
confidence: 99%
“…Equilibrium pressures of mixed-gas hydrates are also moderated by these hydrate formation promoters ( Figure 2). Formation conditions of gas-containing semi-clathrate hydrates and gas hydrates [28,30,31,39,[42][43][44][45][46][47][48]. Double circle represents formation condition in the present study.…”
Section: Gas Separation Using Scmentioning
confidence: 85%
“…Zhang and Lee (2009a) (Arjmandi et al, 2007) and for {H 2 O + (CO 2 + THF)} with a THF molar fraction of 3 percent (Delahaye et al, 2006). CP appears to be a better additive than TBAB to decrease the equilibrium pressure.…”
Section: Cyclopentane: An Immiscible Organic Additivementioning
confidence: 98%
“…The pressure decreased rapidly up to 1%mol of THF, but very slowly above 1%mol for each case study (CO 2 and N 2 ). Delahaye et al (2006) also investigated the hydrate dissociation pressure -temperature data {H 2 O + THF + CO 2 } for THF concentration in the range of 1.6 to 3.0%mol, and the latent heat of dissociation of the mixed hydrates (CO 2 /THF/water). Like Seo et al (2008), the authors observed the drastic reduction of the hydrate pressure formation with a few mole of THF in the system.…”
Section: Tetrahydrofuran: An Example Of Water Soluble Additivementioning
confidence: 99%